Phenolic Compounds and Antioxidant Property of Petal Extracts of Six Lilium Species Native to China - Guo, H.F.; Zhang, Y.L.; Niu, L.X.; Jiao, H.L.; Lei, J.; Luo, J.R. (Asian Journal of Chemistry, 2014)
Lily (Lilium) is used as an important edible and medicinal plant species with long history in China. In this study, petals of six Lilium species native to China were evaluated for their phenolic composition and dietary antioxidant potential. Eleven individual phenolic compounds were analyzed by high-performance liquid chromatography. The results showed that all petal extracts exhibited strong antioxidant activity, which generally correlated positively with the total phenolic contents, total flavonoid contents, total flavanol contents and total anthocyanin contents. Hierarchical cluster analysis showed that L. davidii and L. lancifolium belonged to the group with high phenolic content and high antioxidant activity. L. davidii var. unicolor and L. sargentiae were in the group with moderate phenolic content and antioxidant capacity, while L. brownii and L. leucanthum were clustered in the group with low phenolic content and weak antioxidant activity. It was suggested that lily petals could be used as a potential plant resource of antioxidants for functional food and pharmaceutical applications.